Reconstruction of the molecular evolution of Usutu virus in Germany: Insights into virus emersion and circulation. - Felicitas Bergmann; Cora M Holicki; Friederike Michel; Sabine Bock; Nelly Scuda; Grit Priemer; Susanne Kenklies; Timo Siempelkamp; Jasmin Skuballa; Claudia Sauerwald; Louise Herms; Aemero Muluneh; et al. (Public Library of Science (PLoS), 2023)
Usutu virus (USUV) is a mosquito-borne flavivirus that is widely distributed in southern and central Europe. The zoonotic virus circulates primarily between birds and mosquitoes, can, however, in rare cases infect other mammals including humans. In the past, USUV has been repeatedly associated with mass mortalities in birds, primarily blackbirds and owls. Birds commonly succumb either due to the peracute nature of the infection or due to severe encephalitis. In Germany, USUV has spread rapidly since its first detection in 2010 in mosquitoes under the presence of susceptible host and vector species. Nonetheless, there is to date limited access to whole genome sequences resulting in the absence of in-depth phylogenetic and phylodynamic analyses. In this study, 118 wild and captive birds were sequenced using a nanopore sequencing platform with prior target enrichment via amplicons. Due to the high abundancy of Europe 3 and Africa 3 in Germany an ample quantity of associated whole genome sequences was generated and the most recent common ancestor could be determined for each lineage. The corresponding clock phylogeny revealed an introduction of USUV Europe 3 and Africa 3 into Germany three years prior to their first isolation in the avifauna in 2011 and 2014, respectively. Based on the clustering and temporal history of the lineages, evidence exists for the genetic evolution of USUV within Germany as well as new introductions thereof into the country.